Peritoneal Dialysis for AKI in Cameroon: Commercial Vs Locally-Made Solutions. Issue 4 (July 2018) - Palmer, Dennis; Lawton, William J.; Barrier, Charles; Fine, B.D.; Hemphill, Hayden; Nyah, Norah Ndi; Kinne, Virginie; Ringnwi, Njaprim Ivor; Yong, Genevive; Neufeldt, Amy L.; Mitterand, Yves; Finkelstein, Fredric O.; et al.
Background: Acute kidney injury (AKI) is common in low- and middle-income countries, and is associated with a high mortality. The high mortality rate is in large part due to the inability to perform dialysis in resource-limited settings. Due to significant cost advantages, peritoneal dialysis (PD) has been used to treat AKI in these settings. The costs, however, remain high when commercial solutions are used. Methods: This is a retrospective cohort study of the outcome, and of the peritonitis rates, of patients with AKI treated with either commercially manufactured PD solutions or locally-made PD solutions. A program to treat AKI with PD was started at Mbingo Baptist Hospital in Cameroon. Between May 2013 and January 2015, solutions and connection sets were provided by the Saving Young Lives Program. From January 2015 through March 2017, solutions were locally produced and available tubing was used. Results: Mortality in hospitalized AKI patients was 28% during the period when commercial solutions and tubing were utilized, and 33% when locally produced solutions and available tubing were utilized. In both groups, peritonitis occurred in 16% of treatment courses. Conclusions: Locally produced PD solutions, used with locally available tubing, were used to treat AKI with PD. The mortality and peritonitis rates were similar whether locally produced or commercial supplies were used.